Evaluation of chemiluminescence method for the analysis of plasma homocysteine and comparison with HPLC method in children samples - Gascón,Thais Moura (2010)
ABSTRACT Objective: To compare the results for homocysteine concentration using chemiluminescence and HPLC methods in samples from school-age children. In addition, to determine the reference values for patients of this age group and assess the real prognostic value of homocysteine in healthy children. Methods: A prospective observational study was undertaken to determine plasma levels of homocysteine using two different assays, HPLC and chemiluminescence, in 185 samples from school-age children living in Santo Andre, with no chronic or inflammatory diseases, and absence of pubertal development. Results: The results were presented in percentiles and reference values were determined within this age group (7-9 years old). Homocysteine concentration ranged from 2.0 to 9.9 µmol/l (r = 0.821 and p < 0.001). Conclusions: It was verified that chemiluminescence is comparable to HPLC when both techniques are used to detect homocysteine in school-age children. There is an important correlation between both methods, which allows investigation of this amino acid as a risk factor for heart diseases.